Reconstruction of Gender Thinking between Men and Women as Different Identity in Islam - Ibnu Azka (Jurnal Pemikiran Islam, 2023)
People often interpret gender as the distinction between the sexes of men and women. In English, gender means sex, whereas Webster's New World Dictionary defines gender as the visible differences in values and behavior between men and women. The current understanding of gender often leads to a misunderstanding of its true meaning, resulting in frequent discrimination against women. This article aims to reexamine the established understanding of gender. The study adopts a qualitative descriptive approach to describe, explain, and address the existing issues. The findings of this study demonstrate that men and women, as distinct identities, can attain equality in Islam. Biological differences do not justify a higher or lower position between the two genders. In the Islamic context, there are no specific restrictions preventing women from participating in the public sphere, especially considering the evolving times. The Indonesian context itself exemplifies an increasing presence of women in politics and other domains without violating religious morals.